Fusarium graminearum and Its Interactions with Cereal Heads: Studies in the Proteomics Era - Yang, Fen; Jacobsen, Susanne; Jørgensen, Hans J.; Collinge, David B.; Svensson, Birte; Finnie, Christine (Frontiers in Plant Science, 2013)
The ascomycete fungal pathogen Fusarium graminearum is the causal agent of Fusarium head blight (FHB) in wheat and barley. This disease leads to significant losses of crop yield, and especially quality through the contamination by diverse fungal mycotoxins, which constitute a significant threat to the health of humans and animals. In recent years, high-throughput proteomics, aiming at identifying a broad spectrum of proteins with a potential role in the pathogenicity and host resistance, has become a very useful tool in plant-fungus interaction research. In this review, we describe the progress in proteomics applications towards a better understanding of Fusarium graminearum pathogenesis, virulence and host defence mechanisms. The contribution of proteomics to the development of crop protection strategies against this pathogen is also discussed briefly.